Beyond the sovereign. Practices, margins, and public affairs in Bonnie Honig's democratic theory - Greppi, Andrea; Sánchez Muñoz, Cristina; Velasco Arias, Gonzalo (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
Bonnie Honig’s work constitutes a critical rereading of contemporary democratic theory from the perspective of an agonal politics. Her proposal displaces the sovereign and exceptionalist paradigm to situate democracy as an immanent practice of responding to crisis without suspending the juridical order. Drawing on a reinterpretation of Hannah Arendt and a feminist theory of refusal, Honig explores the material, affective, and performative dimensions of political action. Through figures from classical tragedy, public objects, and affects, she reclaims conflict, disobedience, and imagination as instituting forces. Thus, her thought redefines democracy as a continuous process of interruption, resistance, and institutional reinvention.
Keywords: Bonnie Honig; agonal politics; feminist practices; public things; exceptionalism; democratic emergency; Antigone